PENGAWASAN TERHADAP SYARAT UMUM DAN KHUSUS DALAM PELAKSANAAN PIDANA BERSYARAT - Subekti Budi Utami, Niken (Yustisia, 2012)
AbstractThe probation is an alternative conditional independence revocation entity that is intended to avoid some negative impact from the implementation of the criminal in prison. Implementation of probation committed outside the correctional institution with provisions for prisoners on probation must abide by conditions set by the judge requirements to be supervised by a supervisory officer. The purpose of this study is to investigate the implementation of the supervision of general and specific requirements by the supervisory officer in this case conducted by the supervisory judge observer (kimwasmat), prosecutors and Correctional Center (BAPAS). This research was conducted with library research to obtain secondary data and field research to obtain primary data. In conducting surveillance, kimwasmat never touched prisoner probation supervision, citing a judge's limited ability to perform tasks supervisory oversight of all court decisions, in addition to the obstruction of funding is not budgeted specifically for the task. Supervision conducted by the prosecutor is also not running, because prosecutors had handed over control to BAPAS. The supervision by BAPAS is precisely the effective control, because it is done with two-way method, which offenders are required to report to the office of BAPAS for any particular period and given guidance in the form of mental training and skills. Supervising social each month, also visited a client's home with intent to know the development of coaching. Based on data obtained from BAPAS Yogyakarta during the last year and a half, never breach the terms of which the judge determined, so it can be said implementation of the supervision and coaching successful.